2016
DOI: 10.5301/hipint.5000388
|View full text |Cite
|
Sign up to set email alerts
|

Major Acetabular Defects Treated with the Burch-Schneider Antiprotrusion Cage and Impaction Bone Allograft in a Large Series: A 5- to 7- Year Follow-up Study

Abstract: In a large consecutive series the Burch-Schneider anti-protrusion cage proved to be a valuable option in the treatment of major acetabular bone defects in hip revision surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 41 publications
1
32
0
Order By: Relevance
“…And in our study, complete incorporation was encountered in 25 patients (89%), which achieved good outcome and seems better than Ding (79%) [17]. In previous studies, mid-term result of impaction bone grafting combining with cage showed the failure rate was 0–16% [8, 33, 37]. Recently, Akel et al reported a long-term result of this combination, the failure rate was 8.1% [38].…”
Section: Discussionmentioning
confidence: 49%
“…And in our study, complete incorporation was encountered in 25 patients (89%), which achieved good outcome and seems better than Ding (79%) [17]. In previous studies, mid-term result of impaction bone grafting combining with cage showed the failure rate was 0–16% [8, 33, 37]. Recently, Akel et al reported a long-term result of this combination, the failure rate was 8.1% [38].…”
Section: Discussionmentioning
confidence: 49%
“…Pain levels were considerably reduced and-like in the present study-patients reported a good to excellent overall satisfaction with the surgical results. Re-revision rates were comparable with around 7% [13]. Ilyas et al reported a seven year mid-term follow-up of the classic Burch-Schneider reinforcement ring.…”
Section: Discussionmentioning
confidence: 75%
“…The augment-and-modular-cage system MRS-C has been CEmarked in 2014 and combines the principles of recent acetabular antiprotrusion cages (Ganz [4], Burch-Schneider [13,14]) with a variety of metal buttress augments.…”
Section: Implantmentioning
confidence: 99%
“…32 Despite the limitation of few published clinical trials on the subject, radiation therapy and indomethacin have been investigated in many observational and longitudinal studies. [18][19][20][21][22][23][24][25] However, we observed that the results of these studies were also contradictory and should be interpreted with caution regarding the benefits and the risks of possible adverse effects, such as the risk of cancer when using radiation therapy and the risk of death from bleeding or gastric perforation, as well as pseudoarthrosis when using indomethacin. [18][19][20][21][22][23][24][25] As a strength of this review, we highlight the conduct of a comprehensive survey of randomized clinical trials in any language and with no restrictions on year of publication.…”
Section: Discussionmentioning
confidence: 90%
“…Then, we removed 41 duplicates and deleted 156 articles by screening titles and abstracts. We read 18 full articles, of which 13 were excluded: twelve studies had another type of design than a clinical trial, [18][19][20][21][22][23][24][25][26][27][28][29] and one presented patients from another research published and included in this article. 30 Of the total, five met the inclusion criteria (Figure 1).…”
Section: Resultsmentioning
confidence: 99%